Mitoxantrone as induction treatment in aggressive relapsing remitting multiple sclerosis: treatment response factors in a 5 year follow-up observational study of 100 consecutive patients. Issue 1 (10th September 2007) - Le Page, Emmanuelle; Leray, Emmanuelle; Taurin, Grégory; Coustans, Marc; Chaperon, Jacques; Morrissey, Sean P; Edan, Gilles
Abstract : Background: Mitoxantrone was approved by the French health authority (AFSAPPS) in October 2003 to treat patients with aggressive multiple sclerosis (MS). Objective: To report the long term effectiveness and safety of mitoxantrone as induction therapy in patients with aggressive relapsing–remitting MS, and to assess treatment response factors. Material and methods: 100 consecutive patients with aggressive relapsing–remitting MS received mitoxantrone 20 mg monthly combined with methylprednisolone 1 g for 6 months. Relapses, Expanded Disability Status Scale (EDSS) and drug safety were assessed every 6 months for up to at least 5 years. Within 6 months after induction, 73 patients received maintenance therapy (mitoxantrone every 3 months (n = 21); interferon beta (n = 25); azathioprine (n = 15); methotrexate (n = 7); glatiramer acetate (n = 5)). Results: During the 12 months following initiation of mitoxantrone, the annual relapse rate (ARR) was reduced by 91%, 78% of patients remained relapse free, MRI activity was reduced by 89%, the mean EDSS decreased by 1.2 points (p<10 −6 ) and 64% of patients improved by 1 point or more on the EDSS. In the longer term, the ARR reduction was sustained (0.29–0.42 for up to 5 years), the median time to the first relapse was 2.8 years and disability remained improved after 5 years. Younger age and lower EDSS score at the start of mitoxantrone treatment were predictive of better treatment response. Three patients presented with an asymptomatic decrease in left ventricular ejection fraction to less than 50% (one reversible). One patient was diagnosed with acute myeloid leukaemia (remission 5 years after diagnosis). Conclusion: Mitoxantrone monthly for 6 months as induction therapy followed by maintenance treatment showed sustained clinical benefit for up to 5 years with an acceptable adverse events profile in patients with aggressive relapsing–remitting MS.